PERFORMANCE PROFILING ON ARGENTINA MEN’S VOLLEYBALL TEAM AT TOKYO 2020 OLYMPICS - T. P. Yokesh; A. Deepa; S.Viswanath; G.Mahalakshmi; M.Suresh Kumar (ShodhKosh: Journal of Visual and Performing Arts, 2023)
This study conducts a comprehensive performance profiling of men’s volleyball teams at the Tokyo 2020 Olympics, specifically focusing on both Bronze medal-winning and losing teams. The observation was used to analyze the 34 sets of 8 matches corresponding to the 12 teams participating in the Tokyo Olympics 2020. The performance indicators were performance in all game actions and classifications. The methodology involves analyzing various performance indicators such as attack points, errors, block points, block errors, serve points, serve errors, reception success, reception errors, perfect digs, dig errors, and set errors. Using chi-square statistical analysis, the results showed a significant association between the final classification of reception, setting, attack, block, and defense (p< 0.05) offering nuanced insights into the performance dynamics of men’s volleyball. This research provides valuable guidance for coaches and players in refining strategies for future competitions.